Dual Farnesoid X Receptor/Soluble Epoxide Hydrolase Modulators Derived from Zafirlukast. (19th November 2019) - Schierle, Simone; Helmstädter, Moritz; Schmidt, Jurema; Hartmann, Markus; Horz, Maximiliane; Kaiser, Astrid; Weizel, Lilia; Heitel, Pascal; Proschak, Anna; Hernandez‐Olmos, Victor; Proschak, Ewgenij; Merk, Daniel
Abstract: The nuclear farnesoid X receptor (FXR) and the enzyme soluble epoxide hydrolase (sEH) are validated molecular targets to treat metabolic disorders such as non‐alcoholic steatohepatitis (NASH). Their simultaneous modulation in vivo has demonstrated a triad of anti‐NASH effects and thus may generate synergistic efficacy. Here we report dual FXR activators/sEH inhibitors derived from the anti‐asthma drug Zafirlukast. Systematic structural optimization of the scaffold has produced favorable dual potency on FXR and sEH while depleting the original cysteinyl leukotriene receptor antagonism of the lead drug. The resulting polypharmacological activity profile holds promise in the treatment of liver‐related metabolic diseases. Abstract : Changing targets : The anti‐asthma drug Zafirlukast was used as a lead to develop dual farnesoid X receptor activators/soluble epoxide hydrolase inhibitors. Systematic structural modification produced the desired polypharmacological profile and depleted the drug's original on‐target activity while conserving the favorable molecular scaffold. Optimized compounds engaged the desired targets in cellular settings. The designed multi‐target profile may generate synergies in treating liver‐related metabolic diseases.